Application of blockchain technology in digital music copyright management: a case study of VNT chain platform - Qilong Shi; Yan Zhou (Frontiers in Blockchain)
IntroductionThis paper presents the design and development of a digital music copyright management system, built on the VNT Chain blockchain platform. The system aims to enhance copyright proof and evidence storage, verify the originality of music copyrights, and facilitate secure copyright transactions.MethodsThe system leverages blockchain technology for data integrity and immutability, utilizes the Shazam algorithm to verify music originality, and employs smart contracts to secure transactions. It is composed of six functional modules: user management, copyright registration, copyright trading, infringement monitoring, evidence storage, and music ecology. The system uses blockchain, the InterPlanetary File System (IPFS), and MySQL to manage various business data requirements.ResultsExperimental results show that the registration time for each music piece increased by approximately 1.9 s. Additionally, the average feature fingerprint data for each music piece stored on IPFS consumed about 8 MB, which aligns with the expected system performance criteria.DiscussionThe system meets performance expectations, offering secure and efficient copyright registration and evidence storage. The use of blockchain and IPFS provides a scalable, reliable solution for managing digital music copyrights.